STRATEGI GREENPEACE MEWUJUDKAN NOL DEFORESTASI DI INDONESIA (STUDI KASUS PABRIK ASIA PULP AND PAPER RIAU) (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2023)
The situation of the world's forests is currently receiving attention from many countries due to the problem of deforestation. Indonesia, as one of the countries that has the largest tropical rainforest area in the world, is also facing the problem of deforestation. Indonesia itself has a commitment to achieve zero deforestation, which can be seen from its involvement in the Kyoto Protocol and the Paris Agreement, even to ratify the two agreements. However, deforestation is still common in Indonesia, one of which is triggered by the operation of the Asia Pulp and Paper (APP) company. This situation attracted the attention of Greenpeace to urge the Indonesian government and the APP company to immediately solve the problem of deforestation. The following research locus starts from 2011 to 2018. The conceptual framework used is international norms and ENGO strategies. The results show that Greenpeace's insider and outsider strategy has succeeded in changing APP's attitude to support forest conservation. Greenpeace's outsider strategy is to put pressure on both the Indonesian government and APP's client companies. Meanwhile, Greenpeace's insider strategy was demonstrated through an audience between Greenpeace and the Indonesian government. Keywords: Greenpeace, APP Company, Zero Deforestation, Insider-Outsider Strategy